DINASTI BANI UMAYYAH DI SURIAH - Jabir, Muh. (State Institute of Islamic Studies (IAIN) Palu, 2007)
When the Prophet Muhammad died in 632 AH., the Islamic territory spread out not only in Madinah, but also throughout the Arab peninsula. After Muawiyah bin Abi Sufyan defeated Ali bin Abi Thalib, the fourth caliph of Islam, in the battle of Shiffin, he founded a dynasty called after his name, the Muawwid Dynasty. It was in the epoch of Muawiyah that the style of governance, which in the period of al-Khulaf al-Rasyidun was still democratic, became a monarchic system of governance. From the epoch of Muawiyah’s rule in Damascus onwards, the Dynasty was ruled based on his offspring. Therefore, it was Muawiyah the first political leader of Islam who implemented the monarchic government system throughout the history of Political Islam. Kata Kunci: Dinasti Umayyah, sistem pemerintahan demokrasi, sistem pemerintahan monarki